Utility Theory Application in Decision-Making Behavior for Energy Use and Management: A Systematic Review - Huiying (Cynthia) Hou (Energies)
This paper investigates the application of utility theory in decision-making related to energy use behavior and management practice in the energy sector. By conducting a systematic literature review, this study aims to understand the theoretical and practical applications of utility theory in optimizing energy consumption and management strategies. The review targets a comprehensive collection of academic works that apply utility theory to various aspects of energy use behavior and management decisions, including efficiency initiatives, renewable energy adoption, and sustainable infrastructure development. A systematic literature review methodology was adopted, which encompassed a rigorous selection process to identify relevant studies, followed by a detailed analysis of how utility theory has been employed to influence energy-related decisions in residential, commercial, and industrial settings. The review findings were synthesized to outline the implications for both policy and practice, highlighting the role of utility theory in guiding more efficient and sustainable energy management practices. Through this exploration, the paper provides a discussion on bridging the gap between economic theoretical models and practical energy management applications. It also offers insights into how decision-making influenced by utility theory can lead to enhanced energy efficiency and sustainability. The findings offer valuable guidance for policymakers and energy managers in designing and implementing energy systems and policies that maximize utility while considering environmental and economic impacts. This paper serves to advance the theoretical framework of utility theory and its practical application in energy management, facilitating better-informed strategies that align with global sustainability goals.